Discontinuation of Aspirin in Heartmate 3 Left Ventricular Assist Device. Issue 6 (August 2019) - Lim, Hoong Sern; Ranasinghe, Aaron; Mascaro, Jorge; Howell, Neil
Abstract : Supplemental Digital Content is available in the text.